Proposal for ‘segmented peer review’ of multidisciplinary papers - Dinakaran, Deepak (Transl Oncol, 2020)
We propose a new process for peer review of multidisciplinary journal submissions called ‘segmented peer review’. The current translational research environment increasingly requires complex and multidisciplinary studies that span multiple distinct specialties within a single paper. Such papers present logistic and practical barriers to effective peer review. To address these barriers, papers undergoing segmented peer review require authors to explicitly i) identify each of the areas of expertise required to review the paper, ii) direct each reviewer to the relevant portions of the manuscript, and iii) suggest in-field reviewers. This segmentation of the paper is then followed by a ‘segmented peer review request’ tailored to the expertise of each potential reviewer, with a request to confine his / her review to those ‘in-scope’ aspects of the paper, while de-emphasizing any optional ‘out-of-scope’ comments. Each reviewer indicates the fitness for publication, or suitability for revision, of their particular segment of the manuscript. The segmented peer review process is completed when the editors integrate the segmented peer reviews. We propose segmented peer review as a fit-for-purpose process with tangible advantages for authors, reviewers, and journal editors. It should reduce the specific barriers to publication inherent in the evaluation of multidisciplinary research efforts.